EDXRF for screening micronutrients in lentil and sorghum biofortification breeding programs - Guild, Georgia E.; Stangoulis, James (Springer, 2021)
This study explores the use of energy dispersive x-ray fluorescence (EDXRF) for screening micronutrient concentrations in lentil and sorghum grain for biofortification breeding programs.